Peran Sastra dalam Pendidikan Karakter Anak Usia Dini melalui Cerita Dongeng - Elisabeth Bela; Katharina Woli Namang; Yeremias Bardi (PT PUSTAKA CENDEKIA GROUP, 2025)
Children are small humans who have potential that still needs to be developed. Children have certain characteristics that are unique and different from adults, they are always active, dynamic, enthusiastic and curious about what they see, hear, feel, they seem to never stop exploring and learning. Early childhood (range 0-6 years) is the right time for parents to provide education that helps develop positive behavior in children. Moreover, at this early age is the golden age, where the brain experiences very rapid or explosive development. Early childhood can be said to be repeat imitators, where children will imitate what is seen, heard, felt from their environment. This is because, early childhood does not yet know the boundaries of right or wrong, good or bad, and appropriate. Instilling character values in early childhood is an important step in forming a good personality from an early age. One effective method in character education is through literature, especially fairy tales. The method used is a qualitative method with library research. The results of the study show that fairy tales have great potential in instilling moral values, such as honesty, courage, responsibility, and empathy. Therefore, the use of fairy tales as a medium for early childhood character education is a relevant and effective strategy to support character in early childhood.